Historical Perspectives On The Economic Impact Of The Acropolis On The Athenian Local Economy (Architecture Image Studies, 2025)
This research examines the economic impact of the Acropolis as a major cultural heritage asset on the local economy of Athens, emphasizing its role as a multidimensional economic anchor rather than a narrowly defined tourism site. Adopting a theoretical and analytical research design grounded in cultural economics, tourism economics, and regional development theory, the paper does not rely on primary data collection or econometric estimation. Instead, it employs conceptual synthesis, structured classification of impact channels, and analytical visualization to explore how cultural heritage shapes economic activity through direct, indirect, and governance-related mechanisms. The analysis distinguishes between immediate economic effects, such as visitor spending, employment generation, and public revenues, and broader multiplier pathways that diffuse activity across local supply chains, labor markets, and public budgets. To enhance comparative clarity, the study uses illustrative heatmaps based on ordinal intensity scales, allowing complex interactions to be examined in a coherent visual framework without making causal claims. A third analytical dimension addresses sustainability pressures arising from intensive cultural tourism and evaluates corresponding governance and management levers. The findings highlight the heterogeneous nature of economic impacts and underline the need for differentiated context-sensitive policy responses that balance economic performance with cultural preservation, environmental protection, and social acceptance. The research contributes an integrative, policy-relevant framework for understanding the economic role of cultural heritage and offers a conceptual basis for future empirical research and strategic planning in heritage-based urban economies.